Green Building Design for a Modern Shopping Center in Bengkayang Regency, West Kalimantan - Iin Arianti; Indah Harini; Muhammad Rafani; Nurul Fitriani (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid social, economic, and cultural development in Bengkayang Regency has accelerated the transformation toward a modern society, increasing the demand for integrated commercial and recreational facilities. This study aims to develop a design proposal for a modern shopping center located on Jalan Raya Sanggau Ledo, Bengkayang Regency, West Kalimantan Province, by applying green building principles and contextual architectural approaches. This research employs a qualitative descriptive method, involving literature review, site analysis, and evaluation of design criteria related to modern shopping centers and sustainable architecture. The analysis focuses on environmental aspects, spatial requirements, and the integration of local cultural elements into the design concept. The results indicate that the application of green building strategies, particularly through the use of sun shading systems, effectively optimizes natural lighting and enhances energy efficiency. The proposed design adopts the concept of Building as Nature, derived from Organic Architecture principles, emphasizing harmony between the built environment and natural surroundings. The use of local and natural materials, such as wood, further strengthens the environmental and cultural responsiveness of the design. The planned shopping center occupies an area of approximately 3.000 m² and consists of four floors and a rooftop, strategically located near Rumah Ramin Bantang, a traditional Dayak house, while maintaining appropriate distance from residential zones. In conclusion, integrating green building principles with organic architectural concepts contributes to the development of a modern shopping center design that is environmentally sustainable, culturally contextual, and functionally adaptive to community needs.